2003
DOI: 10.1021/ja037423w
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Cyclizations and Couplings Involving Nickel Enolates

Abstract: A new strategy for effecting cascade cyclization processes using nickel enolates has been developed. Nickel enolates may be cleanly generated by the oxidative cyclization of an enal and alkyne with Ni(0), and the resulting enolate may be functionalized by a variety of alkylation processes. Partially and fully intramolecular versions of the process allow the rapid synthesis of complex polycyclics from simple achiral, acyclic precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 55 publications
1
19
0
1
Order By: Relevance
“…Further synthetic applications of the proposed nickel metallacycle and related metallacycles that are beyond the scope of this Review have also been reported. [23] An alternate mechanism for this class of transformations has been discussed. If the reaction is initiated by Lewis acid promoted oxidative addition of nickel(0) to the enone, then pallyl intermediate 21 would result (Scheme 11).…”
Section: Couplings Of Alkenes With Alkynesmentioning
confidence: 99%
“…Further synthetic applications of the proposed nickel metallacycle and related metallacycles that are beyond the scope of this Review have also been reported. [23] An alternate mechanism for this class of transformations has been discussed. If the reaction is initiated by Lewis acid promoted oxidative addition of nickel(0) to the enone, then pallyl intermediate 21 would result (Scheme 11).…”
Section: Couplings Of Alkenes With Alkynesmentioning
confidence: 99%
“…83 Spirocycle 257 can be synthesized from a simple acyclic precursor using nickel(0) as a catalyst. 84 . When the phenolic group of the starting stilbene is protected, such as methoxylated catechol 258b, then the reaction stops at the quinone stage (i.e., 259b) which further supports the rearrangement mechanism.…”
Section: Oxidative Cyclization Methodsmentioning
confidence: 99%
“…Enol-alkyne reductive cycloadditions [253,254] are also the [3 + 2] cycloadditions. For example, the intramolecular cyclization of the enol-alkyne proceeds in the presence of a nickel catalyst to give a tricyclic single diastereomer in 71% yield, as shown in eqn (27).…”
Section: Azide Alkyne Huisgen Cycloaddition R Copper Catalystsmentioning
confidence: 99%
“…For example, the intramolecular cyclization of the enol-alkyne proceeds in the presence of a nickel catalyst to give a tricyclic single diastereomer in 71% yield, as shown in eqn (27). [254] Monosubstituted conjugated enynes smoothly undergo [4 + 2] homodimerization by the cyclization of the enyne and monoyne cyclization in the presence of palladium catalyst to give styrene derivatives as shown in eqn (28). [255] These [4 + 2] cycloadditions also proceed by the diene and monoyne cycloaddition, [256 -258] and by the enyne and diyne cycloaddition.…”
Section: Azide Alkyne Huisgen Cycloaddition R Copper Catalystsmentioning
confidence: 99%